TELAAH SIMBOLIK POLA METRUM BAHR TAWIL DALAM SYAIR-SYAIR “ALALA” KARYA IMAM AL-ZARNUJI: PENDEKATAN SEMIOTIKA RIFFATERRE - Hikmawati, Masna; Ulfi , Choiril; Ziya'uddin (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2025)
: This study aims to examine the metrical pattern of Bahr Ṭawīl in the ‘Alāla poems by Imam Al-Zarnuji through the lens of Michael Riffaterre’s semiotic approach. Bahr Ṭawīl is known as one of the oldest meters widely used in the classical Arabic poetic tradition. Beyond serving as a rhythmic element, this metrical pattern also carries symbolic meanings closely related to moral and religious messages. The research employs a descriptive qualitative method with philological and semiotic approaches, encompassing text collection, identification of metrical patterns, and symbolic analysis of the rhythmic structure and the hidden messages within the poems. The findings reveal that the use of Bahr Ṭawīl in ‘Alāla is not merely an adherence to the rules of ʿarūḍ, but also embodies symbols of scholarly values, monotheism, and moral reinforcement for the santri (Islamic boarding school students). This metrical pattern functions as a semiotic medium connecting the text, the poet, and the audience, where the hidden meaning (hypogram) is manifested through the selection of specific wazan and rhythmic repetition. These results affirm that Bahr Ṭawīl in Al-‘Alāla serves not only as an aesthetic element but also as a symbolic means of conveying the educational values of the pesantren tradition.